Pulmonary Emphysema Regional Distribution and Extent Assessed by Chest Computed Tomography Is Associated With Pulmonary Function Impairment in Patients With COPD - Gomes, Plácido; Bastos, Hélder Novais e; Carvalho, André; Lobo, André; Guimarães, Alan; Rodrigues, Rosana Souza; Zin, Walter Araujo; Carvalho, Alysson Roncally S. (Frontiers in Medicine, 2021)
Objective: To evaluate how emphysema extent and its regional distribution quantified by chest computed tomography (CT) are associated with clinical and functional severity in patients with chronic obstructive pulmonary disease (COPD). Methods/Design: Patients with a post-bronchodilator FEV1/FVC < 0.70, without any other obstructive airway disease, who presented radiological evidence of emphysema on visual CT inspection were retrospectively enrolled. A QUAntitative Lung Imaging (QUALI) system automatically quantified the volume of pulmonary emphysema and adjusted this volume to the measured (EmphCTLV) or predicted total lung volume (EmphPLV) and assessed its regional distribution based on an artificial neural network trained for this purpose. Additionally, percentage of lung volume occupied by low-attenuation areas (LAA) was computed by dividing the total volume of regions with attenuation lower or equal to -950 Hounsfield units by the predicted [LAA(%PLV)] or measured CT lung volume [LAA(%CTLV)]. The LAA was then compared to QUALI emphysema estimations. The association between emphysema extension and its regional distribution with pulmonary function impairment was then assessed. Results: 86 patients fulfilled the inclusion criteria. Both EmphCTLV and EmphPLV were significantly lower than LAA indices independently of emphysema severity. CT-derived total lung volume significantly increased with emphysema severity (from 6143 ±1295 up to 7659 ± 1264 mL from mild to very severe emphysema, p<0.005) and thus, both EmphCTLV and LAA significantly underestimated emphysema extent when compared to those values adjusted to the predicted lung volume. All CT-derived emphysema indices presented moderate to strong correlations with RV (with correlations ranging from 0.61 to 0.66), TLC (from 0.51 to 0.59), and FEV1 (around 0.6) and DLCO (around 0.6). FEV1 and DLCO were significantly lower, and RV (p < 0.001) and TLC (p < 0.001) were significantly higher with increasing emphysema extent and when emphysematous areas homogeneously affected the lungs. Conclusions: Emphysema volume must be referred to the predicted and not to the measured lung volume when assessing CT-derived emphysema extension. Pulmonary function impairment was greater in patients with higher emphysema volumes and with a more homogeneous emphysema distribution. Further studies are still necessary to assess the significance of CTpLV in clinical and research fields.